Adolescent learning and health behavior during the COVID-19 pandemic - Lestari, Hariati (Public Health of Indonesia, 2022)
Background: COVID-19 pandemic, in its first year, forced restrictions on social, economic, work, education, and religious activities. All activities were diverted and conducted online to avoid exposure to the coronavirus. These online activities had an impact on students, particularly learning behavior and behavior related to health aspects. Objective: This research aimed to analyze adolescent learning and health behavior. Methods: A descriptive method with a cross-sectional study design was used. The research was conducted from November to December 2021 among students of the Faculty of Public Health, Halu Oleo University, Kendari City, South East Sulawesi Province, Indonesia. Data were collected using online questionnaires with Google Forms and were processed using epi info. Results: The impact of the COVID-19 pandemic on adolescents from the aspect of learning behavior was, during the online learning process, many adolescents experienced constraints, such as the lack of optimal internet networks in their areas in rural areas, the limited quota due to the pandemic also had an impact on the economy of students’ parents, power outages and unfavorable weather condition. In addition, changes in adolescent learning behavior became more skilled in using various applications. In terms of health behavior, there was a change in perspective and behavior, which is more sensitive to health, including dietary habits, exercise pattern, and readiness to face the new normal. Conclusion: The students got difficulty learning technically due to online learning, but there were also many positive impacts, namely increasing skills related to the use of technology, social communication, and health behavior.